2014
DOI: 10.1109/tpwrd.2014.2307117
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for the Influence of the Tank Walls in the Zero-Sequence Topological Model of a Three-Phase, Three-Limb Transformer

Abstract: A method is proposed to account for the influence of the tank walls in the topological transient model of a three-phase, three-limb core-type transformer. The influence of the trans- former tank walls as a distributed-parameter hysteretic element is reproduced by solving a diffusion equation that describes the penetration of the plane electromagnetic wave into the depth of the wall. The reliability of the model is validated by comparing its zero-sequence impedances to those measured on a 25-MVA transformer, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 18 publications
(28 reference statements)
2
34
0
Order By: Relevance
“…This value (2.335 T) considers a snapshot of the flux density distribution that corresponds to the worst saturation conditions. This case occurred in many previous works, such as mild steel BS‐4360 material in Charalambous et al, in which the flux density reached 2.21 T, and high‐grain‐oriented silicon steel HiB‐27ZH95 material in Yang et al, in which the flux density reached 2.36 T at the operating flux density of 1.7 T. Furthermore, the MFD distribution for the high‐grain‐oriented silicon steel HiB‐27ZH95 material in 3D magnetization reached 2.18 T in Li et al The flux density of the M‐5 oriented steel material in the core reached 2.36 T in Arslan et al at the operating flux density of 2 T. In Tang et al, the 3D flux distribution results of the fifth lamination layer with SSL 45° mitered joints showed that the operating flux density of M‐6 material reached 2 to 2.53 T. By contrast, the magnetic field distribution of the transformer model obtained by FEM in Yang et al reached 2.87 T when the operating flux density of core material steel 1008 is 2.58 T. In addition, the value of flux densities in limb “A,” and the adjacent yoke is more than 2.5 T for the grain‐oriented steel.…”
Section: Resultssupporting
confidence: 71%
“…This value (2.335 T) considers a snapshot of the flux density distribution that corresponds to the worst saturation conditions. This case occurred in many previous works, such as mild steel BS‐4360 material in Charalambous et al, in which the flux density reached 2.21 T, and high‐grain‐oriented silicon steel HiB‐27ZH95 material in Yang et al, in which the flux density reached 2.36 T at the operating flux density of 1.7 T. Furthermore, the MFD distribution for the high‐grain‐oriented silicon steel HiB‐27ZH95 material in 3D magnetization reached 2.18 T in Li et al The flux density of the M‐5 oriented steel material in the core reached 2.36 T in Arslan et al at the operating flux density of 2 T. In Tang et al, the 3D flux distribution results of the fifth lamination layer with SSL 45° mitered joints showed that the operating flux density of M‐6 material reached 2 to 2.53 T. By contrast, the magnetic field distribution of the transformer model obtained by FEM in Yang et al reached 2.87 T when the operating flux density of core material steel 1008 is 2.58 T. In addition, the value of flux densities in limb “A,” and the adjacent yoke is more than 2.5 T for the grain‐oriented steel.…”
Section: Resultssupporting
confidence: 71%
“…Without affecting numerical calculation results, they stabilize the solution (simulation) by maintaining the current circuit (the physical sense-the way for leakage current), which is especially important when a discrete change of the resistance of a IM circuit occurs, for example, when powered from the frequency converter or in the case of the phase circuit breaking. A similar solution is described in [10].…”
Section: The Implementation Of a Computer Modelmentioning
confidence: 97%
“…The role of inductance L 04 was explained in [4]. Since the modeled five-limb transformers have reinforced yokes (A yoke = 0.6 A leg ), the variation of L 04 in the range [0, L S12 ] does not affect the model behavior, and L 04 was set equal to L S12 .…”
Section: Topological Transformer Modelmentioning
confidence: 99%
“…The role of the off-core fluxes and thus the necessity for a detailed tank model is different for different transformer constructions. The off-core flux is significant in three-limb three-phase transformers, so a transient model of the tank was proposed in [4]. The lesser role of the tank in five-limb transformers is caused by the presence of the end (lateral) core limbs providing the paths for the unbalanced (zero-sequence) flux.…”
Section: Introductionmentioning
confidence: 99%